AKAR-AKAR SOSIOLOGIS PEMIKIRAN HUKUM ISLAM ABU HANIFAH - Fahmi Assulthoni; Moh Safik (LP2M IAI Miftahul Ulum Pamekasan, 2019)
Abu Hanifah as one of the grand fuqaha who is believed to think in the world at the time, now even for an unlimited time is interesting to read. His thoughts are tinkering with the rational logic of Muslim thinkers after competing to find out the basic laws that affect his mindset. Abu Hanifa was the only fiqh scholar who put forward his mind on a problem that was not found in the Qur'an or hadith seen by the Prophet Muhammad. If explored further, it will be known factors that influence the mindset, as well as what is taken into account are social factors. Social factors in this paper such as community factors when Abu Hanifah lived, intellectual factors, professional factors, political dynamics that occur and others. This commentary is important so that the next generation of Muslims knows about the establishment of Islamic law not only having one dimension, but many dimensions that influence it. Abu Hanifah from several existing literature. From this normative study, conclusions from sociological roots that debate the law of Abu Hanifah are needed by several factors, namely geographical-sociological factors, intellectual factors, professional factors, political factors and renewed personal support.